2021
DOI: 10.1093/molbev/msab334
|View full text |Cite
|
Sign up to set email alerts
|

Pif1 Helicases and the Evidence for a Prokaryotic Origin of Helitrons

Abstract: Helitrons are the only group of rolling-circle transposons that encode a transposase with a helicase domain (Hel), which belongs to the Pif1 family. Because Pif1 helicases are important components of eukaryotic genomes, it has been suggested that Hel domains probably originated after a host eukaryotic Pif1 gene was captured by a Helitron ancestor. However, the few analyses exploring the evolution of Helitron transposases (RepHel) have focused on its Rep domain, which is also present in other mobile genetic ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 63 publications
1
11
0
Order By: Relevance
“…Using a large set of eukaryote genomes, we found that HELIANO could quickly produce a range of annotations, from a lack of full-length HLE to predictions of thousands of full-length and non-autonomous copies. We did not predict any HLE using HELIANO on 4,491 bacterial genomes, in accordance with the current model on the evolution of HLEs (46). Similarly, we did not detect HLEs in 139 of the 404 screened eukaryote genomes, a finding underscoring that false positives are not a central issue.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Using a large set of eukaryote genomes, we found that HELIANO could quickly produce a range of annotations, from a lack of full-length HLE to predictions of thousands of full-length and non-autonomous copies. We did not predict any HLE using HELIANO on 4,491 bacterial genomes, in accordance with the current model on the evolution of HLEs (46). Similarly, we did not detect HLEs in 139 of the 404 screened eukaryote genomes, a finding underscoring that false positives are not a central issue.…”
Section: Discussionsupporting
confidence: 87%
“…Recent studies have identified variants of Helitrons named Helentron and Helitron2 (12)(13)(14)(15)(16)(17). To avoid confusion, we will collectively use the term Helitron-like elements (HLEs) to refer to all variants (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These protein sequences showed higher similarity to ScPif1 (38% for AtPLH1, 46% for AtPLH2 and 47% for AtPLH3) as compared to HsPif1 (~30%) (Supplementary Table 2a). A recent study suggested that Pif sequences in Arabidopsis emerged from Helitron/Helentron helicase domains (Heringer and Kuhn, 2022).…”
Section: Identification and Structural Characterization Of Pif-like H...mentioning
confidence: 99%
“…However, Pif1 is related to cancer in humans since mutations in Pif1 have been linked to oncogenesis [ 14 , 15 , 16 , 17 ]. Sequences related to Pif1 were also found in some genomes, mostly of plants and bats, as being part of helitron transposons [ 18 ] and these Pif1-like sequences forming Hel domains of helitron transposases may have originated from bacteria [ 19 ].…”
Section: Introductionmentioning
confidence: 99%